Let Me Think About It—Establishing “Need to Reflect” as a Motivational Variable in Reflection Processes - Hendrik Lohse-Bossenz; Gerlinde Lenske; Andrea Westphal (Education Sciences, 2025)
Reflection is considered to be a core component of professional development in teacher education, yet little is known about the motivational determinants of reflective activities in everyday school contexts. Drawing on theories of learning and motivation, we introduce and conceptualise the “need to reflect” as a situationally and personally influenced motivational factor that mediates the relationship between classroom experiences and subsequent reflective processes. We operationalise this construct through a newly developed item and examine it in a diary study involving N = 79 in-service primary school teachers over ten school days. Multilevel analyses reveal that daily classroom-related hassles—especially failed attempts to address disturbances—are positively associated with teachers’ need to reflect, whereas successful classroom management reduces this need. Furthermore, emotional exhaustion moderates this relationship: Teachers with higher levels of emotional exhaustion reported a stronger link between unsuccessful disturbance management and their need to reflect. Self-efficacy in classroom management is not shown to have a moderating effect. These findings suggest that the need to reflect fluctuates across situations and is influenced by individual teacher characteristics, offering new insights into motivational components underlying reflective processes with significant implications for teacher education and professional development.